2021
DOI: 10.3389/fimmu.2020.624411
|View full text |Cite
|
Sign up to set email alerts
|

Legend of the Sentinels: Development of Lung Resident Memory T Cells and Their Roles in Diseases

Abstract: SARS-CoV-2 is wreaking havoc around the world. To get the world back on track, hundreds of vaccines are under development. A deeper understanding of how the immune system responds to SARS-CoV-2 re-infection will certainly help. Studies have highlighted various aspects of T cell response in resolving acute infection and preventing re-infections. Lung resident memory T (TRM) cells are sentinels in the secondary immune response. They are mostly differentiated from effector T cells, construct specific niches and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…SARS-CoV-2 continues to mutate, changing its surface antigens to escape antibody-mediated neutralization ( 7 ). Thus, memory T cells, in particular lung T RM , are thought to be another crucial immunity in providing effective protection against the spread of viruses and the development of severe diseases ( 70 73 ). In this study, mixing the antigen with rLF can increase IFN-γ producing CD4 + and CD8 + T RM in the lung ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 continues to mutate, changing its surface antigens to escape antibody-mediated neutralization ( 7 ). Thus, memory T cells, in particular lung T RM , are thought to be another crucial immunity in providing effective protection against the spread of viruses and the development of severe diseases ( 70 73 ). In this study, mixing the antigen with rLF can increase IFN-γ producing CD4 + and CD8 + T RM in the lung ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that circulating memory CD8 + T cells can be recruited into the lung and converted into Trm phenotype without antigen recognition (Van Braeckel-Budimir and Harty, 2017 ). Airway T cells are mainly replenished by recruitment from the lung interstitium (Ely et al, 2006 ), and Trm cells in the interstitium receive continuous compensation from circulating Tem cells (Qian et al, 2020 ). However, several studies mentioned that the lung Trm compartment was not replaced by the circulating memory pool (Takamura et al, 2016 ; Van Braeckel-Budimir and Harty, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…T RM and B RM cells are also implicated in the pathogenesis of asthma [73,262]. Specifically, Th2-T RM cells secrete cytokines that promote and sustain airway eosinophilia [72] [262].…”
Section: Asthmamentioning
confidence: 99%
“…T RM and B RM cells are also implicated in the pathogenesis of asthma [73,262]. Specifically, Th2-T RM cells secrete cytokines that promote and sustain airway eosinophilia [72] [262]. Upon HDM exposure, IL-2 signalling enables the generation, migration and retention of allergen-specific Th2-T RM cells in the lungs, where they drive AAI [72].…”
Section: Asthmamentioning
confidence: 99%